Problem solving treatment and group psychoeducation for depression: multicentre randomised controlled trial. Issue 7274 (9th December 2000) - Dowrick, Christopher; Dunn, Graham; Ayuso-Mateos, Jose Luis; Dalgard, Odd Steffen; Page, Helen; Lehtinen, Ville; Casey, Patricia; Wilkinson, Clare; Vazquez-Barquero, Jose Luis; Wilkinson, Greg
Abstract: Objectives: To determine the acceptability of two psychological interventions for depressed adults in the community and their effect on caseness, symptoms, and subjective function. Design: A pragmatic multicentre randomised controlled trial, stratified by centre. Setting: Nine urban and rural communities in Finland, Republic of Ireland, Norway, Spain, and the United Kingdom. Participants: 452 participants aged 18 to 65, identified through a community survey with depressive or adjustment disorders according to the international classification of diseases, 10th revision or Diagnostic and Statistical Manual of Mental Disorders, fourth edition. Interventions: Six individual sessions of problem solving treatment (n=128), eight group sessions of the course on prevention of depression (n=108), and controls (n=189). Main outcome measures: Completion rates for each intervention, diagnosis of depression, and depressive symptoms and subjective function. Results: 63% of participants assigned to problem solving and 44% assigned to prevention of depression completed their intervention. The proportion of problem solving participants depressed at six months was 17% less than that for controls, giving a number needed to treat of 6; the mean difference in Beck depression inventory score was −2.63 (95% confidence interval −4.95 to −0.32), and there were significant improvements in SF-36 scores. For depression prevention, the difference in proportions of depressed participants was 14% (number needed to treat of 7); the mean difference in Beck depression inventory score was −1.50 (−4.16 to 1.17), and there were significant improvements in SF-36 scores. Such differences were not observed at 12 months. Neither specific diagnosis nor treatment with antidepressants affected outcome. Conclusions: When offered to adults with depressive disorders in the community, problem solving treatment was more acceptable than the course on prevention of depression. Both interventions reduced caseness and improved subjective function.